Span-wise fluctuating MHD convective flow of a visco-elastic fluid through a porous medium in a hot vertical channel with thermal radiation - Singh, K.D. (Zielona Góra: Uniwersytet Zielonogórski)
An unsteady mixed convection flow of a visco-elastic, incompressible and electrically conducting fluid in a hot vertical channel is analyzed. The vertical channel is filled with a porous medium. The temperature of one of the channel plates is considered to be fluctuating span-wise cosinusoidally. A magnetic field of uniform strength is applied perpendicular to the planes of the plates.
Keywords: magnetohydrodynamics; MHD; span-wise cosinusoidal; convective; porous medium; radiation